Correlation Between Resected Volume of Prostate and Improvement in International Prostate Symptom Score - Arshad, Majid Khan Kakakhel, Tanveer Ahmad, Shahid Ali, Muhammad Tahir Bashir Malik, Muhammad Asif, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Benign prostatic hyperplasia (BPH) is a common disease in ageing men and prostate resection is common surgical procedure for it. The symptoms of the enlarge prostate can be assessed by using International Prostate Symptoms Score (IPSS). Some studies show that the resected volume of prostate correlates with the prostate symptoms while some show no correlation between symptoms and volume resected. Objective: To find the correlation between resected volume of prostate and IPSS after resection. Study Design: Cross-Sectional Study. Study Setting: Department of Urology, Institute of Kidney Diseases, Peshawar, Pakistan. Study Duration: 01-10-2020 to 30-03-2022. Material and Methods: Pre-operatively, weight and height were measured by digital weight machine and inches tap. Patients symptoms assesses with IPSS for mild, moderate and severe symptoms. Prostate tissue resected during surgery was put in a 60cc syringe and sent to pathologist for exact volume. Post-operatively, patients were followed after one month for symptoms. The difference between pre and post-operative IPSS was calculated. Results: Mean age, prostate volume and change in IPSS were 57.89±14.18 years, 41.05±6.28 ml and 14.84±3.20. There were 34.1% patients each in 30-49 and 50-59 years age groups and 31.8% in 70-80 years group. Pre-operatively, 68.2% patients presented with severe symptoms, 22.7% with moderate symptoms and 9.1% with mild symptoms. Post-operatively, severe symptoms were reduced to 11.4% while moderate symptoms were seen in 52.3% patients. Mean prostate resected was 41.05 grams. Correlation of change in IPSS and prostate volume was 0.280. Conclusion: There was positive correlation between change in prostate volume and IPSS but it was very weak. In other words, the strength of association between these two is very low i.e. r = 0.280 or 7.8% (0.2802) and not statistically significant i.e. P = 0.065. Keywords: Benign prostatic hyperplasia, enlarge prostate, BHP, IPSS, TURP.